Biphenotypic characteristics, cell size and prognosis in childhood acute myeloblastic leukemia - Olcay, Lale; Hiçsönmez, Gönül; Ertem, Ulya; Okur, Hamza; Tuncer, A. Murat (The Turkish Journal of Pediatrics, 1999)
In order to determine the prognostic significance of cell size together with expression of biphenotypic markers in childhood acute myeloblastic leukemia (AML), we evaluated the cell size of children with AML, 12 with and 21 without biphenotypic markers. The patients were followed up for at least 12 months. The cells which were stained with FITC conjugated surface marker antibodies were divided into small, middle or large cell groups according to their mean channel number of forward scatter by flow cytometry. Nine of 12 biphenotypic and 15 of 21 non-biphenotypic children either died or relapsed within the first 12 months. The percentages of the small, middle and large cells were similar in children and in deceased patients, regardless of whether or not they expressed biphenotypic markers. We believe that biphenotypic marker expression is a poor prognostic factor regardless of cell size.